Hubungan Tingkat Pengetahuan Remaja Tentang Merokok Dengan Perilaku Merokok Di SMPMuhammadiyah 1 Kartasura - Hajidolah, Ihsan, Siti Arifah, S.Kp., M.Kes, Dian Nur Wulanningrum, S.Kp., Ns., M.Kep (2015)
Smoke behaviors in Indonesia was one among the highest in the world, 46.8% of men and 3.1% of women with aged 10 years and over were classified as smokers. Smoking habit in adolescents is strongly associated with the interaction, in generally want to be accepted by all age groups and do not want to feel less suitable. The purpose of this study was to the correlation between adolescent knowledge about smoking and smoking behavior in students of SMP Muhammadiyah 1 Kartasura. This research was descriptive correlative study. The sample of this research were 67 male students of class VIII and IX grade at SMP Muhammadiyah 1 Kartasura. The results of research are: (1) the level of students' knowledge about the cigarette in SMP Muhammadiyah 1 Kartasura is moderate, (2) the smoking behavior of students in SMP Muhammadiyah 1 Kartasura mostly smoke, and (3) no the relationship between the level of knowledge of adolescents about smoking and smoking behavior in students of SMP Muhammadiyah 1 Kartasura, where the higher the knowledge that the lower adolescent smoking behavior